2010
DOI: 10.1063/1.3511343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stiffening, bistability, and bit operations in a microcantilever

Abstract: We investigate the nonlinear dynamics of microcantilevers. We demonstrate mechanical stiffening of the frequency response at large amplitudes, originating from the geometric nonlinearity. At strong driving the cantilever amplitude is bistable. We map the bistable regime as a function of drive frequency and amplitude, and suggest several applications for the bistable microcantilever, of which a mechanical memory is demonstrated. © 2010 American Institute of Physics. ͓doi:10.1063/1.3511343͔Microcantilevers are w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 20 publications
1
67
1
Order By: Relevance
“…Potential sources of nonlinearities include: nonlinear electronic components required for signal conditioning [11,12], nonlinear stress-strain relation of the cantilever material subject to large deformations [15,16] and nonlinear forces between the probe and the sample or surrounding viscous fluids [17]. As a result, the dynamics of these systems are often very complex and several cases of chaos [18] and bifurcations [19,20] on the response of the resonators have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Potential sources of nonlinearities include: nonlinear electronic components required for signal conditioning [11,12], nonlinear stress-strain relation of the cantilever material subject to large deformations [15,16] and nonlinear forces between the probe and the sample or surrounding viscous fluids [17]. As a result, the dynamics of these systems are often very complex and several cases of chaos [18] and bifurcations [19,20] on the response of the resonators have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…19 This geometric change has a small but measurable effect on the resonance frequency of all the other vibrational modes. The effect of the cantilever amplitude on its own resonance frequency was recently analyzed in detail; 20 for the first few modes, any nonzero amplitude stiffens the frequency response, and this gives rise to frequency pulling. Recently, we also presented a detailed study on the coupling mechanism between the vibrational modes in clamped-clamped resonators.…”
mentioning
confidence: 99%
“…The feasibility of the use of a nanoelectromechanical system (NEMS) as a memory element has been demonstrated in a number of experimental investigations [1][2][3][4][5][6][7][8] . It has been suggested that in order to increase the frequency of operation, oscillatory states (cycles) should be used as the stationary states of memory elements, with consequential switching between two cycles.…”
mentioning
confidence: 99%